In Defence of the Diversity of Faculty Talents - Juchacz, Piotr W.; Cern, Karolina M. (Adam Mickiewicz University Press, 2013)
The article contributes to the current debate on what activities of the professoriate should be most highly prized. Different obligations generally fall within one of three categories of faculty activities: research, teaching, or – the most unwelcomed - administrative burdens. But the abovementioned activities by no means exhaust the list of duties conducted by the members of a contemporary faculty. Counselling and advising students or service to the public can be mentioned as additional ones between many others. In this article we analyze the problem of the broad range of faculty activities and the issue of the contestable measures of their evaluation within the institutional framework of a university. In our view they address the question of mission ascription to a university or a department and then of an individual scholarly path-taking.
Keywords: threshold of scientific credibility; institutional self-reflexivity; evaluation of faculty activities; third mission of university; issue of the faulty time; domains of scholarship; scholarship of discovery; scholarship of application; scholarship of integration; public scholarship; flexible career path; recognition; identity building; academic faculty; higher education research; roles of university administration; institutional change; higher education reforms; Ernest Boyer; Marek Kwiek